Identity, Place, and Difference: An Autoethnography - Suna Xie (MOZAIK HUMANIORA, 2016)
Identity is a process of becoming, and is thus fluid. The construction of identity is often influenced by many factors, including the place s/he lives in. Identity has always been a work in progress, a process of self-making, adapting and renewing based on different social positions one is placed into voluntarily or obligatory. Being a female from Shanxi province and Chinese, the author feel that these gendered, place located and ethnically classified positions form a key part of her identity shaped by the many places she has lived, both inside and outside China. This paper will be an investigation on how each place, with its own distinct geographical location as well as its political social and cultural dynamic, shaped the author’s identity as a person today, as well as the process of her struggle to negotiate with these multifaceted subject positions as represented by these places. Taking autoethnography as a method of research, the study utilized the author’s reconstructed memories, photographs, and some personal writing she has produced during her time living in places discussed in this article as source materials. This autoethnographic account showed that the experience of living in marginalised positions in different places has enabled the interpretation the social inequality and political injustices from a different perspective. The reflective account helps to understand the existing discourses on Chinese diaspora and realize how the discourses cannot do justice to the complex subjectivities of diasporic experiences.